2022
DOI: 10.21511/ppm.20(1).2022.33
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the population’s social resilience environment (the case of the Carpathian region of Ukraine)

Abstract: The system of indicators of the population’s socio-economic vulnerability is the determinant of regions’ social resilience. The growth of these indicators leads to the emergence of new and aggravation of existing social risks and threats in different time periods. The paper aims to provide a comprehensive assessment of the population’s social resilience environment in the Carpathian region of Ukraine. The environment of the population social resilience in the oblasts of the Carpathian region of Ukraine is asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The law of social networks should become a unifying force capable of resolving many issues related to establishing a clear and precise understanding of the subject (user) of the account, the owner of the social network (for example, it is possible to establish subsidiary liability of the owner of the social network if consumer rights were violated by persons using for illegal purposes fake account), create real legal measures to protect the account. The formation of the law of social networks and the allocation of the corresponding legal institution as an independent one, in need of adequate legal regulation, is an urgent task of our time (Mulska, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The law of social networks should become a unifying force capable of resolving many issues related to establishing a clear and precise understanding of the subject (user) of the account, the owner of the social network (for example, it is possible to establish subsidiary liability of the owner of the social network if consumer rights were violated by persons using for illegal purposes fake account), create real legal measures to protect the account. The formation of the law of social networks and the allocation of the corresponding legal institution as an independent one, in need of adequate legal regulation, is an urgent task of our time (Mulska, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The study suggested a few recommendations and recovery strategies to overcome this unstable situation. Individual activities, foreign assistance, and government support are emphasized in this regard (Mulska et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to its journalists, online media platforms should prioritize engaging returning readers rather than solely focusing on one-time visitors who merely read headlines. Similarly, cultural institutions need to cater to this returning audience, and simply distributing press releases to showcase their activities does not suffice (Mulska, 2022). Editors' valuable time is consumed by verifying such press releases.…”
Section: Ukrainian Literaturementioning
confidence: 99%